Forest euphoria : the abounding queerness of nature - Kaishian, Patricia Ononiwu (Spiegel & Grau, 2025)
Growing up, Patricia Ononiwu Kaishian felt most at home in the swamps and culverts near her house in the Hudson Valley. A child who frequently felt out of place, too much of one thing or not enough of another, she found acceptance in these settings, among other amphibious beings. In snakes, snails, and, above all, fungi, she saw her own developing identities as a queer, neurodivergent person reflected back at her--and in them, too, she found a personal path to a life of science. In Forest Euphoria, Kaishian shows us this making of a scientist and introduces readers to the queerness of all the life around us. Fungal species, we learn, commonly encompass more than two biological sexes--and some as many as twenty-three thousand. Some intersex slugs mutually fire calcium carbonate "love darts" at each other during courtship. Glass eels are sexually undetermined until their last year of life, a mystery that scientists once dubbed "the eel question." Nature, Kaishian shows us, is filled with the unusual, the overlooked, and the marginalized--and they have lessons for us all. Wide-ranging, richly observant, and full of surprises, Forest Euphoria will open your eyes and change how you look at the world.--Publisher's description